Antibiofilm study on osteomyelitic bacteria using new gentamicin-nigella sativa fusion emulsions - Khairul Ikhwan bin Yaakob (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2016)
The treatments of chronic osteomyelitis are difficult, time-consuming and relatively expensive due to the presence of bacterial biofilm that is highly resistant to antibiotics. This study aimed to assess synergistic antibacterial activities of gentamicin-Nigella sativa fusion towards the most common biofilm-bacteria in osteomyelitic infection. Briefly, a total 57 samples (prostheses, bones, tissues and swabs) were taken from 17 cases of osteomyelitic infection at Hospital Tengku Ampuan Afzan, Kuantan. The samples were processed, isolated species were identified, as well as biofilm identification and antibiotic sensitivity assays were performed. Fusion of gentamicin and N.sativa were formulated in 4 different types of emulsions (A, B, C, and D) consisting of constant 0.1% (w/v) gentamicin and different Nigella sativa oil concentrations from 32.5% to 46.6% (v/v). Antimicrobial activities of the emulsions were evaluated using disc diffusion assay and determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Then, the assessment of antibiofilm activities was carried out as pre- and post-biofilm assays. The pre-biofilm consists of biofilm formation inhibition and minimum biofilm inhibition concentration (MBIC). The post-biofilm assay was done to evaluate the effects of the emulsions on the biofilm, using biofilm penetration test and confocal laser screening microscope (CLSM) analysis. It was found that prosthesis (89%) and bone (66.7%) samples produce the most bacteria growth and Staphylococcus aureus (10 out of 16) was the most frequently identified. In the disc diffusion assay, significant synergistic effect of emulsions was seen only in resistant S.aureus (clinical isolate) (Tukey's test p < 0.05). Additionally, emulsions MIC values were up to 10 times lower than gentamicin alone against all S.aureus while MBC values of emulsions were up to 3 times lower towards sensitive S.aureus (clinical isolate and control). No bactericidal activity was exhibited by all compounds tested on resistant S.aureus (clinical isolate). In pre-biofilm evaluation, there were significant differences in biofilm formation inhibition in comparison between these emulsions with N.sativa and gentamicin alone in both clinical isolate S.aureus (sensitive and resistant) (Tukey's test p < 0.05). MBIC values of emulsions were up to 10 times lower than gentamicin against all S.aureus. In contrast, N.sativa alone was lesser than emulsions and gentamicin. For post-biofilm assessment, no significant difference in penetration rate was found between emulsions and gentamicin. As opposed to N.sativa which showed little penetration. In the CLSM analysis, only emulsion C was used. Results revealed that emulsion C significantly reduced the biofilm thickness compared to gentamicin and N.sativa alone (Tukey's test p < 0.05). Furthermore, the surface percentage (%) of non-viable bacteria of emulsions is significantly higher than gentamicin and N.sativa alone (Tukey's test p < 0.05). In conclusion, this new fusion of gentamicin-N.sativa have synergistic antimicrobial and antibiofilm properties towards different strains of S.aureus including resistant strains, thus, can be developed as a new, and customized, gram-positive-specific treatment for ostoemyelitic infection.